Life cycle assessment on alginate-based nanocomposite beads for the removal of lead(II) from aqueous solutions. (February 2022) - Chiew, Christine Shu Ching; Gourich, Wail; Pasbakhsh, Pooria; Poh, Phaik Eong; Tey, Beng Ti; Song, Cher Pin; Chan, Eng-Seng
Abstract: Alginate-based nanocomposite beads have been widely studied as adsorbents for heavy metal removal from aqueous solutions because of their low cost and superior adsorption performance. Additionally, they can be reused after regeneration via desorption for increased sustainability. This paper, for the first time, reports the environmental impacts of incorporating halloysite nanotubes (HNTs) into blank alginate beads, and the impacts of acid regeneration followed by reuse of these beads. We assessed a total of 10 impacts through a life cycle assessment on alginate-HNTs nanocomposite beads for the removal of lead(II) from aqueous solutions. From our results, the incorporation of HNTs into blank alginate beads to improve their mechanical stability and adsorption performance posed insignificant burden to the environment. To produce the beads, the greatest contributor to all environmental impacts was found to be the large quantity of HCl used for the extraction of alginate from seaweed, followed by truck transportation of the beads. Furthermore, the regeneration and reuse of the spent beads reduced all environmental impact categories by at least 72% for the entire life cycle. To improve the sustainability of the beads production, it was suggested to reduce and reuse HCl and water throughout the process, as well as to source for locally produced materials to reduce transportation distances. Graphical abstract: Unlabelled Image Highlights: LCA was performed on alginate-halloysite nanocomposite beads for lead(II) removal. Halloysite improved the mechanical stability and adsorption performance of beads. Incorporation of halloysite caused insignificant environmental burdens. Alginate extraction and beads transportation were the environmental hotspots. Regeneration of spent beads followed by reapplication reduced environmental impacts.